Within‐person dynamics of physiological and perceived stress among South African youth in positive youth development programs - Roya Abbasi‐Asl; Natasha Keces; Richard M. Lerner; Margaret Mackin; Ruoying Zhang; Elizabeth M. Dowling; Jonathan M. Tirrell; Alexa Hasse; Kirsten Olander; Angela Larkan; Chuma Mashita; Raah Msimango; et al. (Applied Psychology: Health and Well-Being, 2026)
Abstract This study investigated weekly within‐person relations between physiological (measured through salivary cortisol) and perceived stress (measured through self‐report) among youth participating in a rural positive youth development (PYD) program in South Africa. Participants ( N = 35, M age = 11.6, SD age = 0.62) took part in an intensive longitudinal study involving 16 weeks of salivary cortisol collection and completion of a brief weekly survey. Using dynamic structural equation modeling, we tested for changes in physiological and perceived stress over time, as well as for autoregressive and cross‐lagged effects. Results revealed a significant decrease in physiological stress over time among youth in the program, whereas perceived stress remained low and stable. We also found that higher stress in 1 week—both physiological and perceived—predicted higher stress in the following week (autoregressive effects), but the two types of stress did not predict one another (cross‐lagged effects), and these relations varied across individuals. These findings suggest that, even within the same PYD program context, different indicators of stress remain distinct and may follow person‐specific patterns. Implications for future PYD research and programs are discussed.